2019
DOI: 10.3389/fnmol.2019.00283
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Specific Reference Genes for MicroRNA Expression Analysis in a Mouse Model of Peripheral Nerve Injury

Abstract: MicroRNAs (miRNAs) have emerged as master switch regulators in many biological processes in health and disease, including neuropathy. miRNAs are commonly quantified by reverse transcription quantitative real-time polymerase chain reaction (RT-qPCR), usually estimated as relative expression through reference genes normalization. Different non-coding RNAs (ncRNAs) are used for miRNA normalization; however, there is no study identifying the optimal reference genes in animal models for peripheral nerve injury. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…Some studies have indicated its unsuitability for miRNA normalization due to expression instability in various experimental conditions [ 31 , 32 , 33 ]. Conversely, in other models, U6 expression levels are very stable among the sample groups, making it a valid endogenous control [ 30 , 34 ]. Concerning the miRNAs present in the plasma, few reference data are available in support of selecting a reliable endogenous reference gene.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have indicated its unsuitability for miRNA normalization due to expression instability in various experimental conditions [ 31 , 32 , 33 ]. Conversely, in other models, U6 expression levels are very stable among the sample groups, making it a valid endogenous control [ 30 , 34 ]. Concerning the miRNAs present in the plasma, few reference data are available in support of selecting a reliable endogenous reference gene.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs are a type of endogenous regulatory ncRNAs found in eukaryotes, which are about 22 nucleotides long 26 . They are initially produced in the nucleus by RNA polymerase II as long primary transcripts (pri-miRNAs), which fold into hairpins to bind to Drosha and Dicer, the RNase III families of enzymes.…”
Section: Classification and Features Of Non-coding Rnasmentioning
confidence: 99%
“…Normalizing against U6 snRNA demonstrates the feasibility of our approach but is not ideal for the following reasons. U6 snRNA expression can vary in mouse tissues (even within the same organ), differ significantly between genders, and be affected by a mouse's age [108,[110][111][112][113]. U6 snRNA expression also likely varies greatly between mouse strains and sub-strains [114,115].…”
Section: U6 Snrna Normalization For Mirna Uptake Should Be Considered Qualitativementioning
confidence: 99%
“…Finally, the calculation of variation between groups of candidate control genes can be accomplished with the NormFinder algorithm [171]. For the best results, these four methods can be used together to determine the optimum reference genes for miRNA quantitation, as recently shown for CNS tissues of mice [108]. Even after optimum reference ncRNA genes have been identified, control RNA gene expression should be monitored in the presence of the miRNA interest to ensure that the control genes are not significantly affected by the miRNA (i.e., ∆Cq = ~0).…”
Section: Going Beyond These Pilot Studiesmentioning
confidence: 99%